RANCANG BANGUN SISTEM KEAMANAN KUNCI SEPEDA MOTOR MENGGUNAKAN E-KTP SEBAGAI TAG BERBASIS ARDUINO UNO - Fauzi, Riza; Priyandoko , Gigih; Setiawidayat, Sabar (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
Security system technology is very important. With a motorbike lock security system using E-KTP as a tag, it is hoped that it can add security to motorbikes. The security system used on motorbikes today is still not safe enough because it still is has a limited security system. Therefore, a additional be tter security systems are needed on the vehicles themselves and are easy to use by the vehicle owner. This research aims to design additional prototypes for Arduino UNO based motorcycle security system that can be used for maintenance motorcycle safety. The method used is to utilize the radio wave frequency from the E-KTP and attach it to the RFID Reader and Arduino UNO. The results and analysis of the testing system are that the maximum reading distance between the E-KTP and the RFID Reader is 1 cm. It is hoped that this research can be used to help fulfill a motorbike security system using E-KTP as a tag with radio Frequency Identification Technology (RFID).